Distinct cellular toxicity of two mutant huntingtin mRNA variants due to translation regulation. - Haifei Xu; Juan Ji An; Baoji Xu (PLoS ONE)
Huntington's disease (HD) is a neurodegenerative disorder caused by CAG repeat expansion within exon1 of the HTT gene. The gene generates two mRNA variants that carry either a short or long 3' untranslated region (3'UTR) while encoding the same protein. It remains unknown whether the two mRNA variants play distinct roles in HD pathogenesis. We found that the long HTT 3'UTR was capable of guiding mRNA to neuronal dendrites, suggesting that some long-form HTT mRNA is transported to dendrites for local protein synthesis. To assay roles of two HTT mRNA variants in cell bodies, we expressed mRNA harboring HTT exon1 containing 23x or 145x CAGs with the short or long 3'UTR. We found that mutant mRNA containing the short 3'UTR produced more protein aggregates and caused more apoptosis in both cultured neurons and HEK293 cells, compared with mutant mRNA containing the long 3'UTR. Although the two 3'UTRs did not affect mRNA stability, we detected higher levels of protein synthesis from mRNA containing the short 3'UTR than from mRNA containing the long 3'UTR. These results indicate that the long HTT 3'UTR suppresses translation. Thus, short-form mutant HTT mRNA will be more efficient in producing toxic protein than its long-form counterpart.